Perception, Preference and Attitude of Nahdlatul Ulama and Muhammadiyah Committee toward Islamic Bank in Indonesia - Hamdan Yuafi; Lailatu Dhilkhijjah; Siti Solikhah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
This research is conducted among Islamic non-governmental organizations;those are Nahdlatul Ulama and Muhammadiyah. This research aims todetermine the perception (X1), preference (X2), and attitude (X3) of Islamicmass organizations or non-governmental organizations in Indonesia towardIslamic Banking and their decision (Y) of using the products of IslamicBanking or Islamic Financial Institutions. We took Branch Board of NahdlatulUlama (PCNU) and the Regional Committee of Muhammadiyyah (PDM)Salatiga as population. The sample in this research is 33 respondents. Thetechniques used are multiple regression analysis and independent sample ttest.Regression result shows that the preference variables have positive  and significant effect on customer’s decision variables. While the perceptionand preference variables do not have a positive and significant effect on thedecision in becoming customer. And the adjusted R square or determinationcoefficient valued 0.690, which means that 69.0% of dependent variable(Y) is affected by the independent variable (X), while 31% dependent variable(Y) is influenced by other variables outside the equation. And the last, independent sample t-test shows that there is no significant differencebetween PCNU and PDM Salatiga in their perception, preference, attitudeand decision toward Islamic Banking